Chlorophyll Extraction from Microalgae: A Review on the Process Engineering Aspects. (18th May 2010) - Hosikian, Aris; Lim, Su; Halim, Ronald; Danquah, Michael K.
Abstract : Chlorophyll is an essential compound in many everyday products. It is used not only as an additive in pharmaceutical and cosmetic products but also as a natural food colouring agent. Additionally, it has antioxidant and antimutagenic properties. This review discusses the process engineering of chlorophyll extraction from microalgae. Different chlorophyll extraction methods and chlorophyll purification techniques are evaluated. Our preliminary analysis suggests supercritical fluid extraction to be superior to organic solvent extraction. When compared to spectroscopic technique, high performance liquid chromatography was shown to be more accurate and sensitive for chlorophyll analysis. Finally, throughCO 2 capture and wastewater treatment, microalgae cultivation process was shown to have strong potential for mitigation of environmental impacts.